2000
DOI: 10.1007/pl00008686
|View full text |Cite|
|
Sign up to set email alerts
|

Complete nucleotide sequence of the Oenothera elata plastid chromosome, representing plastome I of the five distinguishable Euoenothera plastomes

Abstract: We describe the 159,4443-bp sequence of the plastid chromosome of Oenothera elata (evening primrose). The Oe. elata plastid chromosome represents type I of the ®ve genetically distinguishable basic plastomes found in the subsection Euoenothera. The genus Oenothera provides an ideal system in which to address fundamental questions regarding the functional integration of the compartmentalised genetic system characteristic of the eukaryotic cell. Its highly developed taxonomy and genetics, together with a favoura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(9 citation statements)
references
References 30 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…Large inversions are well characterized in the chloroplast genomes of various plant families/genera and the sequence data have been used to determine angiosperm lineages from the genus to phylum level (Jansen and Palmer, 1987; Milligan et al, 1989; Raubeson and Jansen, 1992; Hupfer et al, 2000; Kim and Lee, 2005). In contrast, limited plant groups were studied involving small inversions.…”
Section: Discussionmentioning
confidence: 99%
“…Large inversions are well characterized in the chloroplast genomes of various plant families/genera and the sequence data have been used to determine angiosperm lineages from the genus to phylum level (Jansen and Palmer, 1987; Milligan et al, 1989; Raubeson and Jansen, 1992; Hupfer et al, 2000; Kim and Lee, 2005). In contrast, limited plant groups were studied involving small inversions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that plastomes in many angiosperm lineages have genomic structural differences, called inversions, ranging from small to large inversions, which provide important phylogenetic information ( Figure 2 ). These include Onagraceae ( Hupfer et al., 2000 ), Asteraceae ( Walker et al., 2014 ), Fabaceae ( Wang et al., 2018 ; Charboneau et al., 2021 ), and Commelineaceae ( Jung et al., 2021 ). Previously, Jung et al.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the genomes of typical angiosperms [21][22][23][24], those of Zoysia lack the genes accD, ycf1, and ycf2 and introns in the clpP and rpoC1 genes, which is a pattern observed in most grasses [25][26][27]. The loss of two introns in the clpP gene has been reported independently in different angiosperm families, including Poaceae [28][29][30], the IR-lacking clade of Leguminosae [31], Oleaceae (opposite-leaved Jasminum and Menodora) [32], and Onagraceae (Oenothera) [33].…”
Section: Discussionmentioning
confidence: 99%